The Role of Zhang Qian in the Opening of the Silk Road - Zhang, Aimei (Transactions on Economics, Business and Management Research, 2023)
The mission of Zhang Qian to the Western Regions was a strategic initiative undertaken during the reign of Emperor Wu of the Han Dynasty to address the border crisis posed by the Xiongnu. This involved establishing connections with the Western Regions and implementing a strategic plan to weaken the Xiongnu. In addition to its political objectives and impact, Zhang Qian's mission to the Western Regions made a significant contribution to the opening of the Silk Road.